Analysis of Factor that Affect Financial Performance of PD. BPR Bahteramas Konawe - Hardianto, Hardianto; Wawo, Andi Basru; Sabilalo, Mahmudin A. (PT. Riset Press International, 2024)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Operating Costs and Operating Income (BOPO) on financial performance, as measured by Return On Assets (ROA), at PD. BPR Bahteramas Konawe. Using secondary data from the annual report of PD. BPR Bahteramas Konawe during the 2018-2022 period, this study applies multiple linear regression analysis with classical assumption tests and hypothesis testing to evaluate the effect of these variables, both simultaneously and partially, on ROA. The analytical tool used in this research is SPSS version 25. The results showed that CAR, LDR, NPL, and BOPO together had a positive and significant influence on the ROA of PD. BPR Bahteramas Konawe, indicating that increasing these values in accordance with the BPR health standards set by the Financial Services Authority (OJK) contributes to increasing bank profitability. Partially, CAR has a positive but insignificant effect on ROA, while LDR and NPL have a negative but insignificant effect. The significant negative effect of BOPO on ROA indicates that higher operational efficiency contributes to improved bank financial performance. This research provides new insights in banking finance literature regarding the importance of managing capital, liquidity, credit, and operational efficiency in improving bank financial performance, especially for PD. BPR Bahteramas Konawe in the context of OJK regulations.